Availability and Utilization of the WHO-Recommended Lifesaving Medicines for Under-Five Children at University of Gondar Comprehensive Specialized Hospital, Amhara Region, Ethiopia - Alem Endeshaw Woldeyohanins MSc; Asmamaw Emagn Kasahun MSc; Chilot Abiyu Demeke MSc; Zemene Demelash Kifle MSc (SAGE Publishing, 2021)
According to the World Health Organization report, 5.4 million under-five children died, which is similar to under-five mortality rate of 39 deaths per 1000 live births. This rate is higher in sub-Saharan Africa with 76 deaths per 1000 live births. More than 1 out of every 2 deaths is because of diseases that can be managed with drug of low-cost and high quality. Institutional-based cross-sectional survey was conducted from January to February 2021, at the University of Gondar Comprehensive Specialized Hospital. Statistical Package for the Social Sciences software version 24 was used for data analysis. The results were presented using Figures, tables, and texts according to the nature of the data. The overall average availability of priority medicines was 75% on the day of visit and the average stock-out duration in the last 6 months was 23.85 days. Availability and utilization of priority medicines for the management of antiretroviral infections, Vitamin A deficiency, malaria, and diarrheal cases were high, whereas availability and utilization of suggested medication for neonatal sepsis were very low. A significant proportion of priority diseases was managed by non-priority medications. Medicines supply sources of the country, ministry of health, policymakers as well as facility managers should work in collaboration toward ensuring sustainable and consistent availability of priority medicines through the country. Continues in-service training of healthcare professionals is also mandatory to update themselves with newly developed guidelines, standards, and recommendations.